2014
DOI: 10.1002/cssc.201402888
|View full text |Cite
|
Sign up to set email alerts
|

Plasticizer and Surfactant Formation from Food‐Waste‐ and Algal Biomass‐Derived Lipids

Abstract: The potential of lipids derived from food-waste and algal biomass (produced from food-waste hydrolysate) for the formation of plasticizers and surfactants is investigated herein. Plasticizers were formed by epoxidation of double bonds of methylated unsaturated fatty acids with in situ generated peroxoformic acid. Assuming that all unsaturated fatty acids are convertible, 0.35 and 0.40 g of plasticizer can be obtained from 1 g of crude algae- or food-waste-derived lipids, respectively. Surfactants were formed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…High-quality untargeted analyses also provide the potential for identification of high-value components, which may be utilized by a biorefinery approach for the valorization of algal biomass. Recent work has shown that products such as lipids and protein, which are predominantly used for biodiesel and animal feed, may actually produce high-value commodities such as therapeutics, bio-derived pigments, surfactants, and polymer precursors (Christaki et al 2013;Pleissner et al 2015;Hess et al 2018;Sathasivam and Ki 2018;Sathasivam et al 2019). Due to the difficult economics surrounding bioenergy production from algal biomass, it is more important than ever to include commodity chemicals in the algae production value chain in a biorefinery approach (Dong et al 2016a;Laurens et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…High-quality untargeted analyses also provide the potential for identification of high-value components, which may be utilized by a biorefinery approach for the valorization of algal biomass. Recent work has shown that products such as lipids and protein, which are predominantly used for biodiesel and animal feed, may actually produce high-value commodities such as therapeutics, bio-derived pigments, surfactants, and polymer precursors (Christaki et al 2013;Pleissner et al 2015;Hess et al 2018;Sathasivam and Ki 2018;Sathasivam et al 2019). Due to the difficult economics surrounding bioenergy production from algal biomass, it is more important than ever to include commodity chemicals in the algae production value chain in a biorefinery approach (Dong et al 2016a;Laurens et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrothermal transformation of biomass into biofuels and carbon-based chemicals is a promising technology to deal with the fossil fuel depletion and greenhouse gas emission. [1,2] Depending on the reaction temperatures, thermochemical conversion of biomass can be classified into hydrothermal carbonization (150-250°C), hydrothermal liquefaction (250-350°C), pyrolysis (350-700°C), and gasification (700-1000°C). [3][4][5] In particular, hydrothermal liquefaction (HTL) is a direct thermochemical-conversion of biomass for liquid biofuel production under relatively mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The lactic acid market presents an annual growth of 16.2%, mainly due to the production of polylactic acid and ethyl lactate, whilst the estimated demand for 2025 is 1960.1 kt [1,2]. Lactic acid can be produced biotechnologically from various renewable resources and waste streams such as food waste [3,4,5], mixed bakery waste [6], coffee pulp and mucilage [7,8], algal biomass [9], and lignocellulosic hydrolysates [10] among others.…”
Section: Introductionmentioning
confidence: 99%